Gambaran Kadar Kolesterol Pada Penderita Hipertensi di RSUD Pasar Rebo Jakarta Timur - Rahayu, Cahyawati; Nugroho, Heru Purwanto; Utami, Widha Maulitia Sekar (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Hypertension or high blood pressure is often referred to as the "silent killer" because it usually does not cause any complaints. Hypertension is thesingle largest contributor to heart disease, kidney failure and stroke in Indonesia. About 70% of cholesterol in the blood is synthesized in the liver,while the rest comes from food intake. The purpose of this study was to determine the description of cholesterol levels in patients with hypertension.This study used a descriptive method with a research sample of 64 data on hypertensive patients who performed cholesterol tests. Data collection was carried out at Pasar Rebo East Jakarta Regional Hospital in the period November 2022-April 2023. The results obtained 24 (37.5%) peoplehave abnormal cholesterol levels, with an age range of 65-74 years as many as 9 (14.1%) people and female gender as many as 15 (39.5%) people. Stage 2 hypertension with abnormal cholesterol levels 21 (52.5%) people. Based on the above results, it can be concluded that 24 (37.5%) peoplehave abnormal cholesterol levels, with an age range of 65-74 years as many as 9 (14.1%) people and female gender as many as 15 (39.5%)people. Stage 2 hypertension with abnormal cholesterol levels 21 (52.5%) people. The conclusion is that of the 64 people with hypertension, 40 people had normal cholesterol levels and 24 people had abnormal cholesterol levels. Keywords: Cholesterol, Hypertension, Hypertensive Patients